Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (Tgt) Untuk Meningkatkan Hasil Belajar Matematika Materi Pecahan Di Kelas Ii Sekolah Dasar - Royani, Tatu Maftuhah; Rochmat, Rochmat; D. S., Yosep Farhan Farhan (Universitas Pakuan, 2023)
APPLICATION OF THE TEAMS GAMES TOURNAMENT COOPERATIVE LEARNING MODEL TO IMPROVE LEARNING OUTCOMES OF FRACTION THEORY MATHEMATICS IN CLASS 2 ELEMENTARY SCHOOLSOne of the fields of science studied from the elementary school level is mathematics. Fractions are mathematics learning material that begins to be studied at level/grade II. Fractions are one of the materials that are considered difficult for students. This can be seen from the student learning outcomes that are not in accordance with the criteria for achieving the learning objectives of fractions. Many students have difficulty solving problems related to fractions because they do not understand the concept of fractions. This study aims to determine the effective learning process through the application of the Teams Games Tournament type of cooperative learning model in improving the learning outcomes of fraction material in class II students of Islamic Elementary School Nurul Iman. Data collection was carried out using the individual test method and observation sheets. The results showed that by applying the Teams Games Tournament cooperative learning model to fractional material, students could improve their understanding of the concept of fractions. As much as 80% of students meet the criteria for achieving the learning objectives of fractional material. This shows that the application of the Teams Games Tournament type learning model is effective.